TINJAUAN YURIDIS PELAKSANAAN PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP MAKANAN MIE INSTAN DALAM KEMASAN YANG TELAH KADALUWARSA - Jinner Sidauruk; Nova Sari Simanjuntak (Nommensen Journal of Legal Opinion, 2021)
The Research is motivated to see how The development of economic sector trade produce various types of goods or variations of food. But in the circulation of food in Indonesian special its instants noodles is still a matter to be considered, where consumers are often harmed by violations committed by business actors by selling instants noodles that have expired. Global competition makes business actors justify any means to reap the benefits of one of them by distributing food expired so that they can reduce the number of losses. Writing method used in this journal writing empirical juridical method that essentially examines the law in its application in public life. The hallmark of empirical juridical research is a study that goes from the das sollen gap (theory)to the das sein (practice or reality). The result of this research is Legal protection for consumers related to the circulation of instant noodles expired in Denpasar is worth noting where many consumers not only inDenpasar city feel the loss due to food or beverage expired. With the existence of Law No. 8 of 1999 on Consumer Protection, the guaranteed consumers who feel aggrieved and the Food and Drug Supervisory Agency in his duties only become a medium in coaching for business actors or producers who sell goods or foods that are expired, while in cracking down in the implementation of public health Office. Not only provide guidance, drug and food regulatory agencies can provide recommendations for follw-up by the health service, as well as the consumer community should be more careful in buying food and if they find naughty business actors in terms of selling expired foods can report to the agency drug and food superintendent.